Kobe : Creative Reconstruction - World Bank Group (World Bank, Tokyo, 2018)
The cities of Japan are an exceptional source of learning on competitiveness of cities. They have recovered from disaster, dealt with population influx, industrialized at a rapid pace, responded to environmental challenge, reached the technological frontier, undergone a housing bubble and its collapse, and reconstruction followed by the natural disasters. Today, they face threats of demographic and technological change that are far from unique to the developed world. The Kobe Case highlights important lessons both on reconstruction of the city after a devastating earthquake devising ambitious new designs for devastated areas and building a life sciences cluster in modern era. This research was prepared by the Tokyo Development Learning Center (TDLC) under the auspices of the Social, Urban, Rural, and Resilience Global of the World Bank Group. Its objective is to create a knowledge base on what makes cities competitive, understand job creation at the city level, and capture the unique development experience of Japan for broad dissemination to development practitioners, government officials, academia and the private sector. The team would like to gratefully acknowledge the Government of Japan and its continued support of the Tokyo Development Learning Center (TDLC) program.